Grapes, Wines, and Changing Times: A Bibliometric Analysis of Climate Change Influence - Diego Grazia; Chiara Mazzocchi; Giordano Ruggeri; Stefano Corsi (Australian Journal of Grape and Wine Research)
Climatic conditions play a major role in wine production. Given the increasing impacts and risks posed by climate change, it is important to understand the effects it will have on the wine sector and different wine-producing regions worldwide. This study provides an in-depth examination of the scientific discourse on wine and climate change from 2000 to 2022 by conducting a bibliometric analysis of the literature published on the Web of Science database, which included 1,314 publications. The use of quantitative and qualitative methods allows us to investigate how research has evolved over the years. Our analysis uncovers the most productive countries, institutions, and journals leading the research in this domain, while emphasising the multifaceted approach to studying wine and climate change. Nevertheless, numerous research areas are yet to be adequately explored. Through co-citation analysis and bibliographic coupling, we identify dominant thematic clusters in previous and current scientific literature and reveal emerging research trajectories in this field. The main thematic clusters found include the assessment of climate change effects on viticultural regions worldwide, climate change’s impact on grape composition, and the impact on grape phenology. Our results can be useful not only to understand the main themes studied until now but also to orientate researchers towards less explored aspects and disciplines in scientific research.